2015
DOI: 10.1007/s11011-015-9776-8
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and electrophysiology of retinal and visual pathways in Wilson’s disease

Abstract: We evaluated correlations between positive findings of changes on brain magnetic resonance imaging (MRI) and selected morphological and electrophysiological parameters of the retinal and visual systems in Wilson’s disease. Fifty-eight Wilson’s disease symptomatic patients were divided according to whether they displayed brain changes on MRI (positive, n = 39; negative, n = 19). All participants and healthy control group (n = 30), underwent retinal optical coherence tomography to assess the thickness of macula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 28 publications
4
35
2
Order By: Relevance
“…The morphological changes in the retina influence its proper function. A previous study conducted on patients with WD showed that this degeneration causes retardation of conductivity along the visual pathway, which was confirmed by prolonged VEP latency [ 4 ].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The morphological changes in the retina influence its proper function. A previous study conducted on patients with WD showed that this degeneration causes retardation of conductivity along the visual pathway, which was confirmed by prolonged VEP latency [ 4 ].…”
Section: Discussionmentioning
confidence: 80%
“…A previous study conducted in patients with WD also found retinal thinning in these patients when examined using OCT [ 4 , 8 ]. Brain magnetic resonance imaging (MRI) changes in patients with WD reflects nervous system injury [ 11 15 ].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations